Common Dysregulation of Innate Immunity Pathways in Human Primary Astrocytes Infected With Chikungunya, Mayaro, Oropouche, and Zika Viruses - Geddes, Victor Emmanuel Viana; Brustolini, Otávio José Bernardes; Cavalcante, Liliane Tavares de Faria; Moreira, Filipe Romero Rebello; de Castro, Fernando Luz; Guimarães, Ana Paula de Campos; Gerber, Alexandra Lehmkuhl; Figueiredo, Camila Menezes; Diniz, Luan Pereira; Neto, Eurico de Arruda; Tanuri, Amilcar; Souza, Renan Pedra; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Arboviruses pose a major threat throughout the world and represent a great burden in tropical countries of South America. Although generally associated with moderated febrile illness, in more severe cases they can lead to neurological outcomes, such as encephalitis, Guillain-Barré syndrome and Congenital Syndromes. Astrocytes play a central role in production of inflammatory cytokines, regulation of extracellular matrix and control of glutamate driven neurotoxicity in the central nervous system. Here, we presented a comprehensive genome-wide transcriptome analysis of human primary astrocytes infected with Chikungunya, Mayaro, Oropouche and Zika viruses. Analysis of differentially expressed genes (DEGs), pathway enrichment and interactomes have shown that Alphaviruses upregulated genes related to elastic fiber formation and N-glycosylation of glycoproteins, with downregulation of cell cycle and DNA stability and chromossome maintenance genes. In opposite, Oropouche virus, upregulated cell cycle and DNA maintenance and condensation pathways while downregulated extracellular matrix, collagen metabolism, glutamate and ion transporters pathways. Zika virus infection only upregulated eukaryotic translation machinery and downregulated interferon pathways. Reactome and integration analysis reveals a common signature in downregulation of innate immune response, antiviral response and inflammatory cytokines associated to interferon pathway for all arboviruses tested. Validation of interferon stimulated genes by RT-qPCR corroborated our transcriptome findings. Altogether, our results showed a co-evolution in the mechanisms involved in the escape of arboviruses to antiviral immune response mediated by the interferon (IFN) pathway.